Analysis of Assesment of Arabic Speaking Skill Tasks Based on ACTFL Perspective - Masrun; Hikmah; Ammar Zainuddin; Daud Abdul Quadir Elega (Al-Muyassar: Journal of Arabic Education, 2026)
This study aims to analyze the assesment instrument of speaking skills in Arabic textbooks for grade X published by Ministry of Religious Affairs of Republic of Indonesia based on the ACTFL perspective. Evaluation of speaking skills is assessed through question instruments in textbooks. Students’ abilities can be measured through well-constructed questions, so this study attempts to provide new insights regarding the evalution of speaking skills in Arabic language textbooks. This study is a literature review, data collection techniques using Arabic textbooks for grade X and ACTFL levels and Ali Al-Khulli perspective, data analysis techniques using qualitative content analysis. The results of the study show that all questions for evaluating speaking skills in the textbook are in accordance with the ACTFL perspective, namely: (1) Novice high as many as 8 questions (2) Intermediate mid as many as 8 questions, (3) Intermediate low as many as 1 question, and (4) Advanced high as many as 1 question.